Contemplative Education: Learning Management in Health Promotion and Illness Prevention Practicum - ชิดดี, กรศศิร์; ศิริพันธุ์, ศิริพันธุ์; แก้วเมืองฝาง, รุจา (Princess of Naradhiwas University Journal, 2018)
The learning process of contemplative education is a philosophy of higher education that integrates introspection and experiential learning into academic study, in order to support academic and social engagement, and develop self-understanding as well as analytical and critical capacities, and cultivate skills for engaging constructively with others. It is based on humanism theory. It helps students to learn “who they are”. Management of the learning process in contemplative education promotes student self-directed, and experiential learning. Applied to nursing, a learning model based on contemplative education focuses on health promotion and illness prevention. It is composed of 6 components, including: 1) concept and principle of component model, 2) objectives and expected outcomes of model, 3) results of the model, 4) key concepts of teaching-learning in the model, 5) teaching process of model, and 6) an evaluation or effectiveness of it. The learning dimensions based on the contemplative education is divided into 3 main aspects: goodness, aesthetic and truth, as well as knowledge. The teaching-learning process in health promotion and illness prevention subject had 4 steps, including 1) mindfulness for practice (Hand), 2) teaching for knowledge (Head), 3) experiential learning for creativity and sound mind (Heart), and 4) reflection. These four steps lead to a planning of contemplative learning, including four steps: 1) practice following the concept of contemplative learning, 2) objectives of activities, 3) set of activities, and 4) expected outcomes. The plan was implemented. Learning activities used for promoting peace were mindfulness training and meditation. Mindfulness training with movement, the exchange of learning with the adjustment of the body and being open minded, thinking development activities, and experiential learning were provided